KÜÇÜK HİDROELEKTRİK SANTRALLERİN MODELLENMESİ VE BENZETİMİ - ÖZBAY, EBRU (Fırat Üniveristesi, 2009)
Elektrik enerjisi talebinin hızla artması nedeniyle, küçük hidroelektrik santrallerin önemi gittikçe artmaktadır. Bu nedenle, bu santrallerin kurulabilme olanaklarının ve işletme koşullarının tespit edilmesi gerekir. Bu çalışmada, Türkiye'nin hidroelektrik enerji üretiminde, küçük hidroelektrik santrallerin önemi incelenmiştir. Küçük bir hidroelektrik santralin bilgisayar ortamında, yük-frekans kontrolünü yapabilmek amacıyla, türbin, generatör ve regülatör modelleri oluşturulmuştur. Daha sonra bu modeller birleştirilerek, küçük bir hidroelektrik santral modeli elde edilmiştir. Doğrusal ve doğrusal olmayan türbinli hidroelektrik santral modelleri, farklı yüklenme durumları için çalıştırılarak, güç ve frekansın zamana göre değişimleri elde edilmiştir. Ayrıca, ilimizde bulunan küçük bir hidroelektrik santral, gerçek parametreleri kullanılarak modellenmiş ve yük-frekans kontrolü yapılmıştır.

Importance of small hydroelectric power plants have been increasing more and more because of fast increasing electrical energy demand. Hence, operation conditions and constructible possibilities of the plants must be determined. In this thesis, the role of small hydroelectric power plants in hydroelectric energy production of Turkey has been investigated. In order to carry out load-frequency control of small hydroelectric power plants in computer environment, the models of turbine, generator, and governor have been generated. Small hydroelectric power plant model has been then obtained by being combined these models. Hydroelectric power plant models having linear and nonlinear turbines have been acquired the variations of power and frequency with respect to time by being operated for different load values. In addition, the small hydroelectric power plant in Elazığ has been modeled by being taken into consideration its real plant parameters as well and ultimately presented load-frequency control.
Modelling and simulation of small hydroelectric power plants
Keywords: Elektrik ve Elektronik Mühendisliği